Analisis Sistem Antrean Pengisian Bahan Bakar di SPBU dengan Model Multi Channel Single Phase - Setiawannie, Yuli (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
A queuing system can enhance operational performance by reducing customer wait times and increasing overall satisfaction. Gas station SPBU 14.203.1131 experiences high daily traffic, particularly from motorcycle riders, leading to long queues and customer discomfort. This study aims to analyze the queuing system at the station and identify the key factors contributing to prolonged wait times. The data were collected through a six-day observation of customer arrival patterns at the Pertalite refueling lane. The queuing model applied in this study is the Multi-Channel Single-Phase (M/M/S) model. The analysis indicates that the current system, which utilizes two servers, is not yet optimal. During peak hours (08:00–09:00 WIB), the average number of customers in the system ranges from 1 to 2 motorcycles, with an average waiting time of 0.6 minutes. To enhance service quality and reduce queuing, it is recommended to add an additional server during peak periods. This measure is projected to reduce the average waiting time to 0.41 minutes. Additional recommendations include improving resource efficiency and ensuring the availability of adequate fuel dispensing infrastructure at the station.